1999
DOI: 10.1023/a:1006208419350
|View full text |Cite
|
Sign up to set email alerts
|

G1‐S transition defects occur in most breast cancers and predict outcome

Abstract: Cell cycle deregulation is frequently observed in tumors and has moreover been proposed to be a requirement for tumor development. By analyzing the expression of p27 by immunohistochemistry in 100 primary breast tumors and combining the analyses with our earlier characterization of cyclin E, D1, p16, and the retinoblastoma protein (pRB), we have been able to cover the majority of potential G1-S transition defects and observed that 90% of the tumors had alterations in one or several cell cycle regulatory protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 16 publications
4
45
0
Order By: Relevance
“…As detailed in another report the cyclin E expression in the present cancer material correlated strongly with proliferation (Nielsen et al, 1999) consistent with other studies on colorectal and breast carcinomas (Yasui et al, 1996;Scott et al, 1997). This strong association, observed in the entire material as well as in tumours with low and high cyclin E (data not shown) raises the question whether cyclin E may be associated with other uncharacterized complexes involved in G1/S transition control.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As detailed in another report the cyclin E expression in the present cancer material correlated strongly with proliferation (Nielsen et al, 1999) consistent with other studies on colorectal and breast carcinomas (Yasui et al, 1996;Scott et al, 1997). This strong association, observed in the entire material as well as in tumours with low and high cyclin E (data not shown) raises the question whether cyclin E may be associated with other uncharacterized complexes involved in G1/S transition control.…”
Section: Discussionsupporting
confidence: 93%
“…The tumour material was divided into three equally sized groups regarding p21 positivity, using cut o s at 1 and 5% positive cells. The immunohistochemical expression of p27 has been detailed earlier (Nielsen et al, 1999) and in summary, 5 ± 90% positive nuclei were observed with the majority of tumours expressing more than 50% positive cells. Seventeen out of 59 (29%) tumours expressed less than 50% p27 positive tumour cells and were de®ned as tumours with low expression (Catzevelos et al, 1997).…”
Section: Cyclin E P27 and P21 Determinationmentioning
confidence: 80%
“…These results and those of others (Nielsen et al, 1999) indicate that defects in G1 regulation are involved in breast cancer progression, and that particular defects are indicative of prognosis and of Cyclin A in early stage breast cancer R Michalides et al response to tamoxifen therapy. The relatively weak statistical significance of these associations with prognosis suggests, however, that other interactive factors are involved.…”
Section: Molecular and Cellular Pathologysupporting
confidence: 66%
“…Others have previously seen an association between cyclin E overexpression and survival, either using Western blotting (Porter et al, 1997;Datta et al, 2000;Keyomarsi et al, 2002), histochemistry (Porter et al, 1997;Datta et al, 2000;Keyomarsi et al, 2002), or flow cytometry (Darzynkiewicz et al, 1996;Nielsen et al, 1999). Our study is fundamentally different from those previous studies, as we neither studied the total amount of cyclin E in the tissue nor just the number of cells staining for cyclin E. Instead, we focused on how cyclin E is expressed in relation to cyclin A expression, which is likely to be related to how cyclin E is expressed over the cell cycle.…”
Section: Discussionmentioning
confidence: 99%